Design and fabrication of innovation of goods sanitizer / Muhammad Faeez Haikhal Mohd Fuad - Mohd Fuad, Muhammad Faeez Haikhal (2022)
Sanitize in main things that must do in this pandemic era to prevent us from infected by Corona Virus that is facing the world right now. The pandemic that attacks people worldwide is currently suffering in the world. As the number of infection chances increases the product which develops the so-called innovation of products to reduce the number of infections that occur, either intentionally or indirectly, contacting other persons. This product can prevent us from spreading the virus to others not infected. Thus, the infection can be reduced every day. If this type of virus does not act early, this type of virus can lead to the extinction of the human population. The main objective of this product is, reduce the amount of infection of the virus all over the world